Assessment of city's sustainability performance via Fuzzy Lingustic Scale: East Malaysia case study - Florianna Lendai, Michael Mulok; Helmi, Sumilan; Zainon, Noor Zainura (Elsevier, 2017)
The rapid growth of urbanization is not without any impact to the economic, environmental and even socially. There has been a constant call to develop measurement tool to provide a fair weightage for the urban sustainability indicators. The aim of this research is develop a measurement tool integrating Fuzzy Linguistic Scale to assess sustainability performance and test it on two selected cities; Kuching and Kota Kinabalu were selected due to their geographical location and their demographic similarities. 16 indicators were utilized in this research where the actual data were obtained from secondary sources on the two cities and were associated with the FLS to obtain the city's final value where Kuching scored 0.595 which falls under 'Fair' sustainability performance, and Kota Kinabalu scored 0.642, which falls under 'Good' sustainability performance. The results then lead to 4 hotspots in Kuching and 5 hotspots in Kota Kinabalu which are considered critical areas that needs to be considered for immediate action.